Performance Optimization Of Solar Pv System Over The Gaps Of The Module And Roof For Effective Ventilation Dominic - Yeow, Zong Hui (2020)
The performance of a solar photovoltaic (PV) module drops by 0.35 %/℃ to 0.4 %/℃ as compared its power rating measured as 25 ℃ under standard test condition (STC). In the tropics, PV array installed as a building-attached photovoltaic (BAPV) system experiences high module temperature because 1) the ambient temperature is high. 2) heat of the rear side of the panel cannot be dissipated effectively through convection because the air gap between the rear side of the solar panel and roof is narrow. Therefore, a cheaper solution purpose in this project is to increase the air gap distance by changing the dimension of the existing mechanical supports to promote a better air ventilation to reduce the operating temperature of the solar panel. However, there is lack of research on the optimal air gap distance that can give the optimal cost- effective solution for BAPV systems operating in the tropics. Therefore, it is essential to model the performance improvement via ventilation by changing the air gap distance so that the optimal air gap can be proposed for the industry. In this project, I model and analyze, the effects of how the air gap between the solar panels and metal deck roof affects the performance of the PV panel. The experiment was done by setting up two commercial PV panels in a side by-side configuration. One PV panel has fixed air gap of 12.5 cm in between the panel and the metal deck roof and another one panel was installed in such a way that the air gap distance can be adjusted. Eight DS18B20 temperature sensors were calibrated before attaching at the back of both PV panels. A Raspberry Pi electronic board was programmed as a temperature data logger. The two PV panels were calibrated under the same condition, with the same air gap distance and connected to the same micro-inverter. The experiment was started with adjustment of the air gap distance of 10.5 cm and measurement were carried for 5 days. The subsequent experiment was to increase the air gap by 2 cm and with the same interval of measurement. The experiment was repeated up to an air gap distance of 20.5 cm. The temperature of the PV panel under different air gap distances were compared. Besides, the electricity output of both panels was compared and analysed. As the result, as the air gap increased from 12.5 cm to 20.5 cm, the overall average operating temperature of the PV panel relatively to reference PV panel vi decrease to 1.5 ℃, thereby increase the total electricity generation percentage to 1.3 %. The Ross coefficient value had decreased from 0.0246 ℃ m2 /W to 0.0166 ℃ m2 /W. Hence, it proves that natural ventilation plays a huge role in dissipating the heat of PV panels, which will then increase the electricity generation of the PV panels. Finally, a cost analysis was performed to calculate the extra income can be obtained from electricity selling and the additional cost of the mechanical air gaps from the increment of air gap distance. It shows that for air gap distance of 20.5 cm, a PV system of 90 kW can gain extra energy profit of RM 21140.87 through 21 years of project lifetime under Net Energy Metering (NEM) scheme available in Malaysia.